2017
DOI: 10.1111/gcb.13590
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence tracks seasonal variations of photosynthesis from leaf to canopy in a temperate forest

Abstract: 21Accurate estimation of terrestrial gross primary productivity (GPP) remains a challenge despite its 22 importance in the global carbon cycle. Chlorophyll fluorescence (ChlF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
107
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 67 publications
(109 reference statements)
8
107
1
Order By: Relevance
“…The SIF–GPP relationship was mainly dominated by APAR and also affected by the covariations in LUEp and Θ f (Equations and ). Both LUEp and Θ f vary with environmental conditions (e.g., light, water, atmospheric CO 2 ) and could be positively correlated with each other (Yang et al., , ). Therefore, should a universal SIF–GPP linear relationship exist, at least the variations in LUE p and Θ f among biomes should offset each other (Sun et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SIF–GPP relationship was mainly dominated by APAR and also affected by the covariations in LUEp and Θ f (Equations and ). Both LUEp and Θ f vary with environmental conditions (e.g., light, water, atmospheric CO 2 ) and could be positively correlated with each other (Yang et al., , ). Therefore, should a universal SIF–GPP linear relationship exist, at least the variations in LUE p and Θ f among biomes should offset each other (Sun et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how SIF responds to APAR and environmental factors can help reveal the underlying mechanisms of the observed strong relationship between SIF and GPP. Previous studies suggested that APAR dominated the SIF–GPP relationship, while SIF also contained information on environmental stresses that were closely associated with LUE p (Li, Xiao, & He, ; Walther et al., ; Yang et al., , ). A recent study used GOME‐2 SIF observations as a proxy for GPP to identify the dominant bioclimatic control factors (e.g., VPD, Tmin, soil moisture) that influence primary productivity (Madani et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For these sites, SIF GOME2 was able to capture early‐season photosynthesis that was not captured by either EVI or PRI (Figure S5 and Table S2). A likely explanation for this result is that proxies based on changes in vegetation greenness (i.e., EVI and PRI) fail to capture seasonal photosynthetic activity of evergreen trees, since greenness and photosynthesis are often decoupled for this vegetation type (Verma et al, ; Vicca et al, ; Walther et al, ), whereas SIF is a direct measure of photosynthetic activity (Manish Verma et al, ; Walther et al, ; Yang et al, ). We suspect that EVI and PRI seasonality in these subregions is more likely tracking changes in greenness of intermixed (e.g., subcanopy) annual and deciduous vegetation (Manish Verma et al, ; Verma et al, ; Vicca et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The uncoupling between electron transport and photosynthesis during the dry season suggests that another process, such as photorespiration, was contributing to energy and power reduction (ATP, NADPH, Fd − ) utilization generated in the electron transport chain (Haupt‐Herting & Fock, ; Lawlor & Tezara, ; Martínez‐Ferri, Balaguer, Valladares, Chico, & Manrique, ). Moreover, this uncoupling can add more complexity for obtaining landscape‐level photosynthesis estimates based on the chlorophyll fluorescence signal (Osuna, Baldocchi, Kobayashi, & Dawson, ; Yang et al., ).…”
Section: Discussionmentioning
confidence: 99%